Cloud Computing: An Exploration on Data Integrity and Its Techniques - R. K. Ramesh; K. L. Neela (Asian Journal of Engineering and Applied Technology, 2019)
In the recent years, the cloud computing moves a step forward by providing more services for the individual users and organizations. Each and every technology and systems can be easily integrated with cloud environment. In future lot of new technology will come to play their role. But to make the new technology fulfill their role they surely need a small part of cloud computing. The cloud plays a vital role in managing the data of different users. Users may be individual or organization and they use any cloud deployment model. Cloud provides low cost unpredictable and untraceable storage space to store user’s data. The main aim is to keep the data reliable, available, secure and sharable for the authorized users. But keeping the data secure is a big issue .In a public cloud any one can access the cloud easily. But the CSP or data owner has to prevent the unauthorized user’s access to the cloud. CSP can easily modify or delete the data which are not used by the user for a long time so as to get the storage space .The data integrity problem can be overcome by some different techniques which are proposed in various models .We can surely say that this cloud computing technology will become popular than any other technology.